2007
DOI: 10.1113/jphysiol.2007.131763
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibition differentially shapes transmission in distinct circuits in the mouse retina

Abstract: Diverse retinal outputs are mediated by ganglion cells that receive excitatory input from distinct classes of bipolar cells (BCs). These classes of BCs separate visual signals into rod, ON and OFF cone pathways. Although BC signalling is a major determinant of the ganglion cell-mediated retinal output, it is not fully understood how light-evoked, presynaptic inhibition from amacrine cell inputs shapes BC outputs. To determine whether differences in presynaptic inhibition uniquely modulate BC synaptic output to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(155 citation statements)
references
References 35 publications
(88 reference statements)
8
146
0
Order By: Relevance
“…We did not immunolabel for GABA A α2 subunits because they are not localized to BCs (15). As found previously (4,19,20), our immunolabeling analysis showed that ON, but not OFF BC axon terminals express substantial amounts of GABA C receptors ( Fig. 1 B and D).…”
Section: Significancesupporting
confidence: 53%
See 2 more Smart Citations
“…We did not immunolabel for GABA A α2 subunits because they are not localized to BCs (15). As found previously (4,19,20), our immunolabeling analysis showed that ON, but not OFF BC axon terminals express substantial amounts of GABA C receptors ( Fig. 1 B and D).…”
Section: Significancesupporting
confidence: 53%
“…S1B). Previous electrophysiological studies suggest that GABA A receptors are abundant on axon terminals of BCs (4,19). Using subunit-specific antibodies, we determined the expression of GABA A α-subunits on the axons and dendrites of type 1 and 2 OFF CBCs, type 6 ON CBCs, and RBCs ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Two non-exclusive functional implications arise. First, glycine receptor (glyR)-mediated, GABA receptor (GABAR)-mediated inhibition of bipolar cells may manifest different kinetics that combine with amacrine cell presynaptic release, such that GABA A R-and glyR-mediated inhibition predominantly control the magnitude of bipolar cell glutamate release, whereas GABA Cmediated inhibition controls the timing of bipolar cell glutamate release by increasing its transiency (Eggers and Lukasiewicz, 2011;Eggers and Lukasiewicz, 2006a;2006b;2010;Eggers et al, 2007). Crossover inhibition networks may appropriate these kinetic differences to increase the range and complexity of bipolar cell and ganglion cell responses.…”
Section: γAc Targets Gac Targets and Crossover Inhibitionmentioning
confidence: 99%
“…Elimination of 1 subunit expression leads to a complete loss of both GABA C R expression and GABA C R-mediated function (McCall et al 2002). As a consequence, retinal bipolar cells in GABA C 1 Null mice lack GABA C R-mediated feedback currents without compensatory changes in other inhibitory inputs (Eggers et al 2007) and related components of the electroretinogram are strongly enhanced in GABA C 1 Null mice (McCall et al 2002).…”
Section: Introductionmentioning
confidence: 99%